Aberrantly Expressed Embryonic Protein NODAL Alters Breast Cancer Cell Susceptibility to γδ T Cell Cytotoxicity - Siegers, Gabrielle M.; Dutta, Indrani; Kang, Eun Young; Huang, Jing; Köbel, Martin; Postovit, Lynne-Marie (Frontiers in Immunology, 2020)
Gamma delta (γδ) T cells kill transformed cells, and increased circulating γδ T cells levels correlate with improved outcome in cancer patients; however, their function within the breast tumour microenvironment (TME) remains controversial. As tumours progress, they begin to express stem-cell associated proteins, concomitant with the emergence of therapy resistant metastatic disease. For example, invasive breast cancers often secrete the embryonic morphogen, NODAL. NODAL has been shown to promote angiogenesis, therapy resistance and metastasis in breast cancers. However, to date, little is known about how this secreted protein may interact with cells in the TME. Herein we explore how NODAL in the TME may influence γδ T cell function. We have assessed the proximity of γδ T cells to NODAL in a cohort of triple negative breast tumours. In all cases in which γδ T cells could be identified in these tumours, γδ T cells were found in close proximity to NODAL-expressing tumour cells. Migration of γδ and αβ T cells was similar toward MDA-MB-231 cells in which NODAL had been knocked down (shN) and MDA-MB-231 scrambled control cells (shC). Furthermore, Vδ1 γδ T cells did not migrate preferentially toward conditioned medium from these cell lines. While 24-hour exposure to NODAL did not impact CD69, PD-1 or T cell antigen receptor (TCR) expression on γδ T cells, long term exposure resulted in decreased Vδ2 TCR expression. Maturation of γδ T cells was not significantly influenced by NODAL stimulation. While neither short- nor long-term NODAL stimulation impacted the ability of γδ T cells to kill MCF-7 breast cancer cells, the absence of NODAL resulted in greater sensitivity of targets to γδ T cell cytotoxicity, while overexpression of NODAL conferred resistance. This appeared to be at least in part due to an inverse correlation between NODAL and surface MICA/B expression on breast cancer target lines. As such, it appears that NODAL may play a role in strategies employed by breast cancer cells to evade γδ T cell targeting, and this should be considered in the development of safe and effective γδ T cell immunotherapies.